2020
DOI: 10.4329/wjr.v12.i8.142
|View full text |Cite
|
Sign up to set email alerts
|

Review of radiographic findings in COVID-19

Abstract: The purpose of this study is to review the published literature for the range of radiographic findings present in patients suffering from coronavirus disease 2019 infection. This novel corona virus is currently the cause of a worldwide pandemic. Pulmonary symptoms and signs dominate the clinical picture and radiologists are called upon to evaluate chest radiographs (CXR) and computed tomography (CT) images to assess for infiltrates and to define their extent, distribution and progression. Multiple studies atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 63 publications
4
25
0
1
Order By: Relevance
“…However, many of the imaging findings in COVID-19 can be nonspecific, and there can be occasional discrepancies between the imaging and clinical features seen in these patients[ 7 , 8 ]. Moreover, on occasions, extrapulmonary disease may dominate in some patients, and pre-existing major illnesses (such as heart failure, liver diseases, chronic kidney disease and malignancies) with the acquisition of COVID-19 illness may pose additional diagnostic dilemmas[ 9 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, many of the imaging findings in COVID-19 can be nonspecific, and there can be occasional discrepancies between the imaging and clinical features seen in these patients[ 7 , 8 ]. Moreover, on occasions, extrapulmonary disease may dominate in some patients, and pre-existing major illnesses (such as heart failure, liver diseases, chronic kidney disease and malignancies) with the acquisition of COVID-19 illness may pose additional diagnostic dilemmas[ 9 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the sparse data in the literature on radiography in the COVID-19 context[ 34 ], the consolidation is the most common finding in the radiographs of infected patients, being predominantly observed in peripheral areas of the lower zones[ 35 ], with a peak of severity 10-12 d after the onset of symptoms[ 36 ]. Among 9 patients in Korea, the CXR detected parenchymal abnormalities in three of them, most with peripheral consolidation that was later confirmed by CT[ 37 ].…”
Section: What Do the Imaging Exams Show About The Disease?mentioning
confidence: 99%
“…It has been reported that >80% of nonsurviving patients suffer from ARDS and/or respiratory failure, often with associated cardiovascular injury ( 3 – 6 ). The lungs of patients with COVID-19 are subject to interstitial mononuclear cell infiltration and edema ( 7 , 8 ), characteristic outcomes in ARDS ( 9 ).…”
Section: Introductionmentioning
confidence: 99%